Ausbeute der Kernreaktion Ni60 (Vi, 2n) Cu60 - Radicella, Renato; Rodríguez, J.; Baró, G. B. B.; Hittmair, Otto (Springer Berlin Heidelberg, 1958)
Fil: Radicella, Renato Comisión Nacional de Energía Atómica; Argentina